2000
DOI: 10.1111/1468-2338.00150
|View full text |Cite
|
Sign up to set email alerts
|

Trends and developments in east central European industrial relations

Abstract: This article overviews developments in industrial relations in the Czech Republic, Hungary and Poland since the fall of the communist regimes in 1989, and assesses the extent to which key developments in these countries reflect both change and continuity from the communist period. We explore the four main institutions through which industrial relations have been conducted: trades unions, workers' councils, employer organisations, and the tripartite arrangements involving representatives of unions and employers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Within the first decade of transformation, membership levels dropped from around 90% to between 20 and 35% (Cox and Mason, 2000). These developments were accompanied by the declining coverage rates of collective agreements and the decentralization of collective bargaining.…”
Section: Similar Pressuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the first decade of transformation, membership levels dropped from around 90% to between 20 and 35% (Cox and Mason, 2000). These developments were accompanied by the declining coverage rates of collective agreements and the decentralization of collective bargaining.…”
Section: Similar Pressuresmentioning
confidence: 99%
“…However, most of the literature on the subject consists of either descriptive single-case studies (Kubínková, 1999;Gardawski, 2001;Héthy, 2001;Tóth, 2001) or of more general pieces that treat the region as the unit of analysis (Kubicek, 1999;Cox and Mason, 2000;Crowley, 2001). Only a handful of more comparative studies point to certain cross-national differences in terms of either the importance assigned to tripartite negotiations, or to organizational and political capacity of unions (Thirkell et al, 1998;Pollert, 1999;Orenstein and Hale, 2001), but even they do not engage into a rigorous comparative analysis that would enable them to either systematically define these differences or more clearly conceptualize their causes.…”
Section: Similar Pressuresmentioning
confidence: 99%
See 1 more Smart Citation
“…By 2000, assessments of the trade union movement in post-communist states suggested that its role was declining and peripheral (Cox and Mason, 2000), with little capacity for collective action (Gall, 2013). This pessimism was compounded by claims about the existence of widespread scepticism about organizational participation in political parties and trade unions (Martin and Cristescu-Martin, 2004).…”
Section: Organizational Resourcesmentioning
confidence: 99%
“…In CEE economies, working conditions for women have deteriorated in recent years in most cases (Pollert, 2005). In CEE countries, there has been a failure of tripartism (Cox & Mason, 2000;Ost, 2000), and industrial relations remain highly fragmented. In Poland, while 24,000 trade unions are registered, the two main trade unions, OPZZ and Solidarity, are still strong rivals (Meardi, 2002).…”
Section: Contrasting Industrial Relations Systemsmentioning
confidence: 99%